Pengaruh Pendidikan, Produk Domestik Regional Bruto, dan Realisasi Belanja Daerah Terhadap Tingkat Kemiskinan di Kepulauan Nias - Laras Ayu Dita; Herlitah Herlitah; Fatimah Fatimah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to see whether there is an influence between education proxied by the average length of schooling, gross regional domestic product (GRDP), and the realization of regional expenditure on poverty in the Regency / City of Nias Islands. The research method of this article is a quantitative method with multiple linear regression analysis techniques. The data used in this study are secondary data obtained through the central statistics agency and the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance in the form of panel data from five regencies / cities in Nias Islands in 2014-2023. Based on the partial analysis results, the education variable and the realization of regional expenditure have a positive and significant effect on the poverty rate. Meanwhile, gross regional domestic product and has a negative and significant effect on poverty in the Nias Islands region, which is seen from the probability value which is smaller than (0.05). The research variable can explain the Y variable by 0.950220 or 95% and the rest is explained by other variables outside the study.